DETERRING RUSSIA AND THE STRATEGIC NARRATIVE ON THE RUSSIAN THREAT IN INNOVATED DEFENSE POLICIES IN THE EUROPEAN UNION - Igrutinović, Milan (National interest, 2024)
The paper deals with the publicly expressed logic of deterring Russia, which is understood as a security threat, in the valid doctrinal documents of the European Union and member states, adopted after Russia's attack on Ukraine in February 2022. First, the declarative attitudes towards the war and the role of Russia, the positioning of Russia as an immediate and long-term security threat are analysed. Those positions are understood as elements of strategic macro narratives about the Russian threat. It then outlines new steps taken to deter the real or perceived threat from Russia, from increasing military budgets to developing military industries. These steps are then analysed in the light of the formal competencies of the European Union in the field of defense, which are minor in relation to military control and capacity, bearing in mind national competencies and the role of NATO, and are much more related to the development of the military industry and technological solutions with a military purpose. The author's conclusion is that there is an established strategic narrative at the EU level that fixes the role of Russia as a security threat. Against such a threat, the processes of arming, innovating military doctrines, and developing the military industry have been launched, which have the function of deterring Russia for a foreseeable long period, and without the particular regard to the immediate outcome of the war in Ukraine.
Keywords: war in Ukraine; Russia; European Union; member states; deterrence; strategic narrative; security and defence strategies